KETERSEDIAAN PRODUK SAMPING TANAMAN DAN INDUSTRI PERTANIAN SEBAGAI PAKAN TERNAK MENDUKUNG PENINGKATAN PRODUKSI DAGING NASIONAL (Forum Penelitian Agro Ekonomi, 2024)
One of main components to boost cow meat is feed availability. In Indonesia, feed availability is still deal with decrease of pasture, competing feed with other uses, such as industry, and limited feed distribution system.  Limited conventional feed sources could be overcome through use of feed from side products of crops and agricultural industry such as rice, oil palm, and sugarcane. This paper reviews livestock capacity potency and identifies new development region potency for beef cow farm business using side products of crops and agricultural industry. Feed availability potency is based on simple calculation of previous studies.  It is estimated that feed source from crops and agricultural industry of rice, oil palm, and sugarcane is around 121.69 million tons of dried matter or it has capacity of 77.42 million livestock units. Based on feed raw material availability region, the potential regions for beef cow farm business development using main feed from side products of crops and oil palm agricultural industry are the provinces in Sulawesi, Papua and West Papua. The beef cow producing regions in Java could utilize side products of crops and processing industry of sugarcane and rice straw. Bali and NTT are regions with feed deficits. To boost beef cow farm business in new development regions, it is necessary: (a) to strengthen researches on processing technology of crop and industrial side products, and quality feed formulation with cheap price, (b)  to introduce complete feed processing technology to the side products potential centers, (c) to develop cheap, complete feed industry for sales.